Algumas experiências profissionais acerca da construção do diagnóstico do TDAH - Schicotti, Rosana Vera De Oliveira; Abrão, Jorge Luis Ferreira; Gouveia Júnior, Sérgio Augusto (Universidade Federal Fluminense, Departamento de Psicologia, 2016)
Abstract This article delves into the professional experiences occurred during the period from 2005 to 2009; its main subject deals with the construction of diagnosis of Attention Deficit Disorder / Hyperactivity Disorder (ADHD). The practices exercised by a guidance counselor and psychologist, along with a Professor, produced many problematizations. These experiences were all derived from critical historical references which found that the diagnosis of ADHD may be taking the place of several absences and conflicts in contemporary times, such as the difficulty of dealing with the diversity of the different modes of existence, as well as with establishing prohibitions and moral values in order to guide the interaction with all human multiplicity.

Resumo Este artigo versa sobre experiências profissionais ocorridas entre 2005 e 2009 e tem como tema a construção do diagnóstico do Transtorno do Déficit de Atenção/Hiperatividade (TDAH). As práticas exercidas por uma orientadora educacional e psicóloga e por um professor produziram questionamentos derivados de referenciais histórico-críticos os quais constataram que o diagnóstico do TDAH pode estar ocupando o lugar de diversas ausências e conflitos na contemporaneidade, tais como a dificuldade de lidar com a diversidade dos diferentes modos de existência e a de estabelecer interditos e valores morais para nortear a convivência com toda a multiplicidade humana.
Some professional experiences about the construction of diagnosis of ADHD
Keywords: ADHD; discipline; childhood; youth; postmodernity; TDAH; disciplinamento; infância; juventude; pós-modernidade